Effect of pre - soaking seed treatments on seed quality parameters of Ashwagandha (Withania somnifera) - J.B. SURYAWANSHI; M.T. BHINGARDE; D.V. DESHMUKH; S.U. WAGHMODE (Seed Research, 2026)
The present investigation entitled, "Seed germination and growth studies in ashwagandha (Withania somnifera)" was carried involving different pre-soaking seed treatments with different chemicals viz., GA3, @soaking 100 ppm for 6 hr (T₂), GA3, soaking @ 200 ppm for 12 hr (T3), GA3, soaking @ 400 ppm for 6 hr (T4), KNO3, soaking @ 1% for 6 hr (T5), KH2,PO4, soaking @ 1% for 6 hr (T6), Thiourea soaking @ 0.5% for 6 hr (T7), Cow urine soaking for 6 hr (T8) and untreated seeds i.e. control (T1). All the pre-soaking seed treatments had significant effect on root yield and growth contributing characters. The pre-soaking seed treatments significantly influenced the growth and root yield contributing characters of ashwagandha. The maximum root yield was observed in the GA3, 400 ppm soaked for 6 hr, followed by GA3, 200 ppm soaked for 12 hr and 1% KNO3, soaked for 6 hr. The seeds pre-soaked with GA3, @ 400 ppm took less number of days for field emergence, days to 50% flowering, higher shoot length, shoot diameter, shoot dry weight, root length, root diameter and root dry weight followed by GA3, @ 200 ppm and 1% KNO3. The root shoot ratio of seeds soaked with GA3, @ 400 ppm recorded significantly superior root-shoot ratio than untreated seeds. Seed quality parameters viz., germination percentage, shoot length, root length, seedling dry weight and vigour index were improved by presoaking seed with GA3, 400 ppm for 6 hr followed by GA3, 200 ppm for 12 hr and 1% KNO3, for 6 hr. The seed germination method was also standardised using different methods viz., between paper, top of paper and sand method at different temperatures viz., 20+2°C, 25+2°C and 30+2°C. Seed germination was significantly influenced by the germination method and temperature. The higher germination percentage (62.67%) was recorded in top of paper method and 25+2°C temperature.